COMPARATIVE VIRULENCE IN ISOLATES OF TILLETIA INDICA AND HOST RESISTANCE AGAINST KARNAL BUNT OF WHEAT - H. M. Zia Ullah; M. I. Haque; C. A. Rauf; L. H. Akhtar; M. Munir (Journal of Animal and Plant Sciences, 2012)
Wheat that becomes unacceptable for human consumption, emitting fishy smell of trimethylamine due to karnal bunt of wheat (Tilletia indica), affects the international wheat trade extensively, owing to quarantine restrictions on germplasm movement across the borders. Applying boot inoculation technique, 39 host wheat genotypes of varied pedigrees were, inoculated with teliospores collected from various isolates separately, obtained from seven districts of Southern Punjab. Differences of disease reactions among the all test genotypes as well as of virulences among the isolates were highly significant. There was also a significant genotype-isolate interaction indicating the gene-for-gene relationship among the host and the pathogen. Isolates collected from Lodhran (Kbm) and Khanewal districts (Kbj), were more virulent followed by isolates of Bahawal Nagar (Kbi), Bahawal pur (Kbs), Rahim Yar Khan (Kbw) and Multan (Kbp) districts respectively, while the virulence capacity of the isolate from Vehari region (Kbn), in their comparison was the lowest of all as characterized by susceptibility category. Significant positive correlation between percent infection and extent of fungal colonization existed. Genotypes/cultivars Punjnad-1, V032862, V033010, V056041, V056132, V066211, V066213, Shafaq-06 and Kiran were classed as resistant against the mixture of isolates, while Inqilab-91, Fareed-06, FSD-85, Bwp-79, Satluj-86, Uqab-2000, AS-2002, Manthar-03, Lasani-08, Chakwal-50, Sahar-06 and Bwp-2000 exhibited moderately susceptible and susceptible response. No cultivar was found immune to karnal bunt of wheat. The possible increase in the virulent patterns of diverse forms of the pathogen stresses to continue conventional breeding strategies for genetic resistance, while the variability analysis of isolates of Tilletia indica will support to explore new sources of resistance in bread wheat.
Keywords: Karnal bunt; comparative virulence; Tilletia indica